RIFM fragrance ingredient safety assessment, 2-methylpropyl pentanoate, CAS Registry Number 10588-10-0. (15th December 2020) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Abstract: The existing information supports the use of this material as described in this safety assessment. 2-Methylpropyl pentanoate was evaluated for genotoxicity, repeated dose toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data from read-across analog ethyl 2-methylbutyrate (CAS # 7452-79-1) show that 2-methylpropyl pentanoate is not expected to be genotoxic and provide a calculated margin of exposure (MOE) > 100 for the repeated dose toxicity and reproductive toxicity endpoints. Data from read-across analog isoamyl acetate (CAS # 123-92-2) show that there are no safety concerns for 2-methylpropyl pentanoate for skin sensitization under the current declared levels of use. The phototoxicity/photoallergenicity endpoints were evaluated based on ultraviolet (UV) spectra; 2-methylpropyl pentanoate is not expected to be phototoxic/photoallergenic. The local respiratory toxicity endpoint was evaluated using the threshold of toxicological concern (TTC) for a Cramer Class I material; exposure is below the TTC (1.4 mg/day). The environmental endpoints were evaluated; 2-methylpropyl pentanoate was found not to be persistent, bioaccumulative, and toxic (PBT) as per the International Fragrance Association (IFRA) Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., Predicted Environmental Concentration/Predicted No Effect Concentration [PEC/PNEC]), are <1. Highlights: 2-Methylpropyl pentanoate; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.